UNRUPTURED CEREBRAL ANEURYSM IN VASCULAR NEUROSURGERY (International Educators Conference, 2025)
Vascular neurosurgery is a diverse field focused on surgical and interventional treatment of cerebrovascular disease, both the manifestations as well as the underlying causes. Specifically, the common diseases that fall in the domain of vascular neurosurgery include cerebral ischemia and ischemic stroke including occlusive vascular disease, non-lesional hemorrhagic vascular disease – which includes spontaneous, hypertensive and angiopathic intracerebral hemorrhage (ICH) – and lesional hemorrhagic vascular disease – which includes cerebral aneurysms, arteriovenous malformations, and cavernomas.